A Critique of Trade Disputes Settlement Mechanism in Nigeria: 1968 to 2004 - Anyim, Francis Chukwudike (University of Lagos, 2009)
Full texts attached
Keywords: Conflict Manifestation; Labour market research; Marxist Perspective; Process of Collective Bargaining; Strike and its effect

E-Commerce and Mobile Commerce in South Africa: Regulatory Challenges - Jobodwana, Z. Ntozintle (Journal of International Commercial Law and Technology, 2009)
E-commerce refers to all forms of commercial transactions that involve individuals and organizations based on the electronic processing of data. Mobile commerce (M-commerce) is the buying and selling of goods and services using mobile telephones or personal digital assistants (PDA). M-commerce is emerging in Africa and South Africa especially as either a complement or an alternative to e-commerce as originally conceived, though there are arguments that mobile telephone technology â€œm-commerceâ€ will surpass â€œe-commerceâ€ as the method of choice for digital commerce transactions. This paper identifies the challenges in adopting e-commerce/m-commerce practices for economic development and competition in International trade. The liberalisation of the telecommunications sector on which e-commerce and m-commerce practices depend is being given priority by the majority of African governments. Despite advances in e-commerce and m-commerce practices in Africa, the growth of e-commerce and m-commerce has been slow. Impediments include low levels of internet penetration and limited communication infrastructure. To meet this problem, the UN adopted through the UN Commission on International Trade (UNCITRAL), Model Law on E-Commerce to help in the harmonisation of e-commerce/m-commerce related laws. Challenges are identified and recommendation made on how to improve the regulatory framework and create an environment conducive to investment and economic development.

Status Ambiguity and Conflict in the Market - Tan, David (Emory University, 2009)
My main theoretical contention is that status hierarchies provide a source of guidance to firms for resolving disputes. A status hierarchy implies a system of deference rules among firms. When disputes arise, deference rules can provide a basis for shared expectations and protocols of conduct about how technical ambiguities should be resolved. In many contexts, technical merit is difficult to assess. However, deference rules can operate as social conventions to which firms default, helping to align potentially incompatible expectations. Within this general framework, my dissertation examines how competitors in the semiconductor industry manage uncertain and frequently overlapping patent rights. In practice, patent rights are highly imperfect legal instruments when it comes to demarcating each firm's contributions to innovation in the industry. Patent disputes arise because of the ambiguity this creates about how much of the collective market returns to innovation each firm is entitled to receive. Despite the prolific patenting and propensity for disputes, the industry has remarkably not ground to a halt from runaway litigation. Litigation events, while significant, are rare. I suggest that this degree of order is, at least partly, attributable to status processes. Status can operate as a stabilizing force in the market, helping to generate orderly competition in the face of disputes. To examine whether this is the case in the semiconductor industry, I theorize that disputes are less easily resolved when the parties involved face greater status ambiguity, i.e. are less clearly differentiated from one another in status. Under status ambiguity, deference rules lose the rule-like, universal quality that makes them persuasive in resolving disputes. This has two consequences. First, firms facing low status ambiguity are less likely to be involved in patent litigation than are firms facing high status ambiguity. Patent litigation events represent failures to resolve patent disputes out of court. Second, firms facing low status ambiguity increase their product line sizes more than do firms facing high status ambiguity. The threat of difficult-to-resolve patent disputes represents a cost that can deter firms from bringing products to market.
Keywords: Litigation; Patent; Semiconductor; Status